Synthesis and characterization of 1′-C-cyano-2′-fluoro-2′-C-methyl pyrimidine nucleosides as HCV polymerase inhibitors. Issue 5 (1st March 2015) - Kirschberg, Thorsten A.; Mish, Michael R.; Zhang, Lijun; Squires, Neil H.; Wang, Ke-Yu; Cho, Aesop; Feng, Joy Y.; Fenaux, Martijn; Babusis, Darius; Park, Yeojin; Ray, Adrian S.; Kim, Choung U.
Graphical abstract